2015
DOI: 10.1177/1069397115591479
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Trust in Ecuador, the United States, and Zimbabwe

Abstract: This study examined the patterns of variables that predict interpersonal trust in three distinct countries. Findings indicated that interpersonal trust is highest in the United States, followed by Ecuador and Zimbabwe. A similar ordering occurred with perceptions of social cohesion, whereas the reverse order occurred for perceptions of competition for scarce resources. Path analyses indicated that perceptions of social cohesion positively predicted interpersonal trust in all three cultures, whereas perceptions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…Further in terms of commitment, “…high uncertainty-avoidance cultures may have a greater need for control (Hofstede, 1980), suggesting a higher threshold of perceived control is necessary for a commitment bond to form” (Klein et al, 2012: 142). Such a conjecture is consistent with research examining Ecuadorian trust more specifically (Mealy et al, 2015). Also, in countries like Ecuador where high power distance is likely, the bonds between employees tend to be much stronger than the bond between employees and the organization (Cheng et al, 2003), which is likely reinforced based on Ecuadorian middle manager’s view of leadership (Vliert and Einarsen, 2008).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Further in terms of commitment, “…high uncertainty-avoidance cultures may have a greater need for control (Hofstede, 1980), suggesting a higher threshold of perceived control is necessary for a commitment bond to form” (Klein et al, 2012: 142). Such a conjecture is consistent with research examining Ecuadorian trust more specifically (Mealy et al, 2015). Also, in countries like Ecuador where high power distance is likely, the bonds between employees tend to be much stronger than the bond between employees and the organization (Cheng et al, 2003), which is likely reinforced based on Ecuadorian middle manager’s view of leadership (Vliert and Einarsen, 2008).…”
Section: Discussionsupporting
confidence: 88%
“…Given the generally scarce resources, Ecuadorians tend to trust one another more than other countries that are more economically viable; however, such trust is also damaged more when social cohesion is low (Mealy et al, 2015). For example, Ecuador was shown to have greater levels of work–family conflict than other countries in the region since Ecuadorian men often had to leave their families to find stable work (Poelmans, 2003).…”
Section: Ecuadormentioning
confidence: 99%
“…However, unlike Beierlein, Kemper, et al (2014a), who found small positive associations of Openness and Conscientiousness with interpersonal trust, we found zero correlations for both the UK and Germany. With regard to internal locus of control, optimismpessimism, and external political efficacy, we could replicate the findings of the German-language source version: Consistent with previous findings, including those of Beierlein, Kemper, et al (2014a), we found-for both the UK and Germany-stable small-to-medium positive relations with internal locus of control (e.g., Massari & Rosenblum, 1972;Stimpson & Maughan, 1978), optimism (e.g., Mealy, Stephan, Mhaka-Mutepfa, & Alvadoro-Sanchez, 2015;Schweer, 2006), and external political efficacy (e.g., Koller, 1992;Schiffman et al, 2010;Schyns & Koop, 2010). Individuals high in optimism and external political efficacy had a higher propensity for interpersonal trust.…”
Section: Correlations With Convergent and Discriminant Constructssupporting
confidence: 90%
“…First, we intended to explore whether the priming–trust relationship can be replicated among Chinese participants. Given that the antecedents of influence may differ across cultures (Mealy, Stephan, Mhaka‐mutepfa, & Alvarado‐Sanchez, 2015), such replication is necessary for generalization of the finding. Second, we wanted to examine whether such an effect could be mediated by person perception, situation perception, or both.…”
mentioning
confidence: 99%